Gambaran Kecenderungan Perilaku Self Injury pada Siswa SMP - Anapichania, Tasya; Nurfarhanah, Nurfarhanah (Lembaga Yasin AlSys, 2024)
This research is motivated by the phenomenon of junior high school students who have difficulty channeling negative emotions when facing problems. Self-injury behavior will have a negative impact on students, therefore students are expected to be able to carry out positive activities to vent their negative emotions. The objectives of this study are (1) to describe the tendency of students' self-injury behavior, (2) to describe the tendency of students' self-injury behavior from the environmental dimension, (3) to describe the tendency of students' self-injury behavior from the biological dimension, (4) to describe the tendency of students' self-injury behavior from the cognitive dimension, (5) to describe the tendency of students' self-injury behavior from the affective dimension and (6) to describe the tendency of students' self-injury behavior from the behavioral dimension. The method used is quantitative descriptive, with a sample of 49 students and the instrument used is a self-injury behavior tendency instrument with a Likert scale. The results of the study showed that: (1) the tendency of self-injury behavior in students as a whole is in the moderate category (56.44%), (2) the tendency of self-injury behavior in students from the environmental dimension is in the moderate category (55.10%), (3) the tendency of self-injury behavior in students from the biological dimension is in the moderate category (61.22%), (4) the tendency of self-injury behavior in students from the cognitive dimension is in the low category (48.98%), (5) the tendency of self-injury behavior in students from the affective dimension is in the moderate category (42.86%) and (6) the tendency of self-injury behavior in students from the behavioral dimension is in the moderate category (46.94%). Based on the results of this study, it is recommended that guidance and counseling teachers provide services to reduce the tendency of self-injury behavior in students in the form of information services, individual counseling services, group counseling services and group guidance services.